SOSIALISASI DAN PELATIHAN DAGUSIBU OBAT SEBAGAI UPAYA PENCEGAHAN PENGOBATAN YANG TIDAK RASIONAL DI MASA PANDEMI COVID 19 - R.K. Saputri; T.A. Hutahaen; D.I. Pramesti; N. Farlina (Buletin Udayana Mengabdi, 2023)
Drugs are materials that function as pain relievers and/or disease healers. Recently, many irrational behaviors related to drug use, such as self-medication , that can increase irrational medication. The solution to the problems offered is the socialization and training of DAGUSIBU and monitoring implementation of DAGUSIBU. DAGUSIBU is an acronym for get, use, store and dispose of drug which becomes a series when getting and consuming drugs. The form of activity carried out is community capacity building with the type of program providing DAGUSIBU socialization and training on proper medicine. Activities consist of DAGUSIBU outreach and training activities using counseling and simulation methods, monitoring and evaluating the implementation of DAGUSIBU via WhatsApp for one month. The results of the activity showed that 85.29% targets had knowledge about DAGUSIBU drugs in the good category, 88.23% of the targets were able to use, dispose and store drugs properly, and 67.65% of targets had applied DAGUSIBU correctly. This activity was said to be successful based on the results of an increase in the level of knowledge in the good category of 55.88%, an increase in skills regarding drug handling after program implementation of 88.23%. Keywords: socialization, training , DAGUSIBU